Ibn khaldun his life and work - Enan, M. A. ([S.l.] : Kazi Publications, 1986)
Within a short compass, the book gives a fair indication of Ibn Khaldun's patterns of thought and meassures, their historic worth, comparing them with the heritage of later scholars and philosophers. The present work gives in popular language a full review of Ibn Khaldun's life from original sources and an analysis of his worth. It abounds in useful information about the work of a remarkable thinker of Islam.